(untitled) (Eurasian Journal of Humanities and Social Sciences, 2021)
The article describes the possibilities of using the principle of interdisciplinary connection in the formation of knowledge, skills and competencies in renewable energy sources in physics education. Also, the results of pedagogical experiments on the teaching of "Elementary concepts of solar photovoltaics" are presented and analyzed.